En prekær situation - Midlertidighed, stabilitet og værdi blandt løstansatte videns- og kulturarbejdere i København og Malmø - Hemmet,Bastian Mollerup (2020)
In this study I address the phenomenon of precarious labour among young knowledge- and cultural workers in southern Scandinavia. Based on seven semi-structured interviews I investigate how precarious labour can be perceived as a liminal state of in-betweenness and ambiguity, which affects the individual in different areas of life. By causing a constant sense of temporality the effects span financial and social concerns, but also raise issues with long-term planning, the ability to become established, and self-identification as fully transitioned into adulthood. This affects the individual perception of personal value and uncovers a system of values of labour, that governs the actions and preferences of the precarious worker. I conclude that the liminal characteristics of precarious labour has a noteworthy effect on the wellbeing of the precarious worker.
Keywords: Socialantropologi; Prekært arbejde; Midlertidigt arbejde; Liminalitet; Værdi